The role of middle managers in knowledge management implementation to improve organizational performance - Al- Hakim, Laith Ali Yuusif; Hassan, Shahizan (2011)
The purpose of this paper is to clarify the role of middle managers in knowledge management implementation toward improving organizational performance. Conceptually, this paper seeks to identify the direct relationship between middle managers role and knowledge management implementation.In addition, it seeks to identify the direct relationship between knowledge management implementation and organizational performance improvement. These relationships have been developed based on holistic of knowledge, resource based view and knowledge based view theories.The methodology used was the intensive reviewof previous studies in this area. In today's business environment, the knowledge management implementation has become as a lifeline of contemporary organizations. Therefore, the organizations must choose the best way to implement knowledge management. However, the complexity of knowledge management implementation has been increased due to lack of an integrated framework of KM implementation. The paper finds that middle managers role can be in place to pave the way to ensure the successful implementation of knowledge management, which is reflected in the organizational performance improvement.By taking an in-depth look at previously disconnected research, this paper offers a conceptual framework that explained how the new role of middle managers came to influence on successful knowledge management implementation. Furthermore, how the successful knowledge management implementation lead to improve organizational performance.